2017
DOI: 10.3389/fphy.2017.00002
|View full text |Cite
|
Sign up to set email alerts
|

RFEA Measurements of High-Energy Electrons in a Helicon Plasma Device with Expanding Magnetic Field

Abstract: In the inductively coupled plasma of the Njord helicon device we have, for the same parameters as for which an ion beam exists, measured a downstream population of high-energy electrons emerging from the source. Separated measurements of energetic tail electrons was carried out by Retarding Field Energy Analyzer (RFEA) with a grounded entrance grid, operated in an electron collection mode. In a radial scan with the RFEA pointed toward the source, we found a significant population of high-energy electrons just … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
30
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 39 publications
12
30
0
Order By: Relevance
“…Other groups have also reported hints of energetic electrons in their expanding helicon source plasmas. 35,44,45 Prior work in our own laboratory found a strong correlation between enhanced upstream density and the appearance of the downstream ion beam. For rf coupling levels that did not result in formation of an ion beam, the upstream plasma density was lower than when a beam formed.…”
Section: Discussionmentioning
confidence: 92%
“…Other groups have also reported hints of energetic electrons in their expanding helicon source plasmas. 35,44,45 Prior work in our own laboratory found a strong correlation between enhanced upstream density and the appearance of the downstream ion beam. For rf coupling levels that did not result in formation of an ion beam, the upstream plasma density was lower than when a beam formed.…”
Section: Discussionmentioning
confidence: 92%
“…As the downstream neutral pressure increases, the electric field at z ¼ 164 cm undergoes significant changes in amplitude, particularly along the edges of the plasma where energetic electrons are observed to stream out from the source into the expansion chamber. 17,25 The energetic electrons create an annulus of increased plasma density through enhanced ionization upstream and downstream of the source-expansion chamber junction. The radius of the annulus maps along the divergent magnetic field to a radius of one electron skin depth from the rf antenna in the plasma source.…”
Section: Resultsmentioning
confidence: 99%
“…The excitation of the helicon wave often produces a high density plasma downstream of the source due to the wave propagating in the plasma column 32 . Several experiments in the expanding magnetic fields have shown that the high density conics are formed in the magnetic nozzles [33][34][35][36] . Two-dimensional measurement of an electron energy distribution has indicated that the high temperature electrons heated by the rf antenna field are transported along the expanding magnetic field 37 .…”
Section: Magnetic Nozzle Radiofrequency Plasma Thruster Approaching Twenty Percent Thruster Efficiency Kazunori Takahashimentioning
confidence: 99%